Influence of preoperative anti‐cancer therapy on resectability and perioperative outcomes in patients with pancreatic cancer: Project study by the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery. Issue 2 (1st August 2013) - Motoi, Fuyuhiko; Unno, Michiaki; Takahashi, Hidenori; Okada, Takaho; Wada, Keita; Sho, Masayuki; Nagano, Hiroaki; Matsumoto, Ippei; Satoi, Sohei; Murakami, Yoshiaki; Kishiwada, Masashi; Honda, Goro; et al.
Abstract Background Little is known about the effects of neoadjuvant therapy on outcomes in patients with pancreatic cancer. This study evaluated the effects of neoadjuvant therapy on resectability and perioperative outcomes. Methods A total of 992 patients were enrolled, with 971 deemed eligible. Of these, 582 had resectable tumors and 389 had borderline resectable tumors, and 388 patients received neoadjuvant therapy. Demographic characteristics and peri‐ and postoperative parameters were assessed by a questionnaire survey. Results The R0 rate was significantly higher in patients with resectable tumors who received neoadjuvant therapy than in those who underwent surgery first, but no significant difference was noted in patients with borderline resectable tumors. Operation time was significantly longer and blood loss was significantly greater in patients who received neoadjuvant therapy than in those who underwent surgery first, but there were no significant differences in specific complications and mortality rates. The node positivity rate was significantly lower in the neoadjuvant than in the surgery‐first group, indicating that the former had significantly lower stage tumors. Conclusions Neoadjuvant therapy may not increase the mortality and morbidity rate and may be able to increase the chance for curative resection against resectable tumor.